2016
DOI: 10.1177/0271678x15610339
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of soluble tumor necrosis factor with preservation of membrane tumor necrosis factor is associated with neuroprotection after focal cerebral ischemia

Abstract: Microglia respond to focal cerebral ischemia by increasing their production of the neuromodulatory cytokine tumor necrosis factor, which exists both as membrane-anchored tumor necrosis factor and as cleaved soluble tumor necrosis factor forms. We previously demonstrated that tumor necrosis factor knockout mice display increased lesion volume after focal cerebral ischemia, suggesting that tumor necrosis factor is neuroprotective in experimental stroke. Here, we extend our studies to show that mice with intact m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 99 publications
2
60
0
Order By: Relevance
“…Using the open field, rotarod, and Y-maze tests, we previously demonstrated that mTNF Δ/Δ mice display no obvious behavioral abnormalities [12]. This was further validated in the present study using the EPM test.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…Using the open field, rotarod, and Y-maze tests, we previously demonstrated that mTNF Δ/Δ mice display no obvious behavioral abnormalities [12]. This was further validated in the present study using the EPM test.…”
Section: Resultssupporting
confidence: 75%
“…Homozygous mTNF Δ/Δ and mTNF wt/wt littermates were obtained by crossing heterozygous mTNF Δ/wt mice at the Biomedical Laboratory, University of Southern Denmark (SDU) [12, 21]. These mice were originally generated by replacing the endogenous TNF allele with Δ1–9, K11E TNF allele [21].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations